Implementing newer agents for the management of castrate‐resistant prostate cancer: what is known and what is needed?. (15th July 2014) - Mottet, Nicolas; Clarke, Noel; De Santis, Maria; Zattoni, Filiberto; Morote, Juan; Joniau, Steven
<x xml:space="preserve">Abstract</x> Men receiving androgen‐deprivation therapy will in time develop metastatic castrate‐resistant prostate cancer (mCRPC). Whilst effective treatment options for mCRPC have traditionally been limited, new agents are becoming available. Since 2010, the number and class of agents available to treat mCRPC has increased dramatically. As such, there is a need for clear guidance on the optimum treatment and sequence of treatments for mCRPC before and after chemotherapy. This evidence‐based statement, reflecting the views of the authors, provides suggestions on the continued relevance of conventional approaches to first‐ and second‐line treatment in mCRPC, the potential role of novel treatments, and factors that may influence the choice of hormonal agents and/or chemotherapy.